Books that cook : the making of a literary meal - Cognard-Black, Jennifer, 1969-; Goldthwaite, Melissa A., 1972- (NYU Press, 2014)
Organized like a cookbook, Books that Cook: The Making of a Literary Mealis a collection of American literature written on the theme of food: from an invocation to a final toast, from starters to desserts. All food literatures are indebted to the form and purpose of cookbooks, and each section begins with an excerpt from an influential American cookbook, progressing chronologically from the late 1700s through the present day, including such favorites asAmerican Cookery, theJoy of Cooking, andMastering the Art of French Cooking. The literary works within each section are an extension of these cookbooks, while the cookbook excerpts in turn become pieces of literature-forms of storytelling and memory-making all their own. Each section offers a delectable assortment of poetry, prose, and essays, and the selections all include at least one tempting recipe to entice readers to cook this book. Including writing from such notables as Maya Angelou, James Beard, Alice B. Toklas, Sherman Alexie, Nora Ephron, M.F.K. Fisher, and Alice Waters, among many others, Books that Cookreveals the range of ways authors incorporate recipes-whether the recipe flavors the story or the story serves to add spice to the recipe. Books that Cookis a collection to serve students and teachers of food studies as well as any epicure who enjoys a good meal alongside a good book.